Awareness and knowledge of HPV, cervical cancer, and vaccines in young women after first delivery in São Paulo, Brazil - a cross-sectional study - Aoki Aline L; Longatto-Filho Adhemar; Costa Maria C; Andreoli Maria A; Pagliusi Sonia; Villa Luisa L; Rama Cristina H; Eluf-Neto José (BMC, 2010)
Abstract Background The success of HPV vaccination programs will require awareness regarding HPV associated diseases and the benefits of HPV vaccination for the general population. The aim of this study was to assess the level of awareness and knowledge of human papillomavirus (HPV) infection, cervical cancer prevention, vaccines, and factors associated with HPV awareness among young women after birth of the first child. Methods This analysis is part of a cross-sectional study carried out at Hospital Maternidade Leonor Mendes de Barros, a large public maternity hospital in Sao Paulo. Primiparous women (15-24 years) who gave birth in that maternity hospital were included. A questionnaire that included questions concerning knowledge of HPV, cervical cancer, and vaccines was applied. To estimate the association of HPV awareness with selected factors, prevalence ratios (PR) were estimated using a generalized linear model (GLM). Results Three hundred and one primiparous women were included; 37% of them reported that they "had ever heard about HPV", but only 19% and 7%, respectively, knew that HPV is a sexually transmitted infection (STI) and that it can cause cervical cancer. Seventy-four percent of interviewees mentioned the preventive character of vaccines and all participants affirmed that they would accept HPV vaccination after delivery. In the multivariate analysis, only increasing age (P for trend = 0.021) and previous STI (P < 0.001) were factors independently associated with HPV awareness ("had ever heard about HPV"). Conclusions This survey indicated that knowledge about the association between HPV and cervical cancer among primiparous young women is low. Therefore, these young low-income primiparous women could benefit greatly from educational interventions to encourage primary and secondary cervical cancer prevention programs.